Auditors and vulnerable communities: a training proposal for university students - Cohetero-Hernández, Dulce Nayeli; González-Quiñones, Fidel (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
This investigation focuses on the proposal and validation of a training program for intervenors prepared to intervene in vulnerable groups. The formulation was constructed with bibliographic sources and with collaborative work with experts in this field in the States of Veracruz and Chihuahua; the validation was done by consulting experts in the State of Chihuahua, analyzing the relevance of each construct of the program with the Delphi technique. The results showed the importance of training intervenors to conceive projects and visualize the target populations focusing on development possibilities rather than vulnerabilities, which should be understood as relative and not inherent. The proposal is based on collaborative work, both in the training of intervenors and in the design, application and evaluation of the interventions to be executed, seeking the integration of the target population in activities traditionally designed for program coordinators or intervenors. The importance of the auditor being trained in the knowledge and respect of the environment and traditions of the communities to be intervened is highlighted, so that their proposed development goal is compatible with the values and cosmogony of said community. Finally, the study discovered the need to advocate for the use of indicators, SWOT analyses and budgets in social interventions.